2018
DOI: 10.2993/0278-0771-38.3.406
|View full text |Cite
|
Sign up to set email alerts
|

Ethnoichthyology of Artisanal Fisheries from the Lower La Plata River Basin (Argentina)

Abstract: We conducted structured surveys using photographs of 88 fish species grouped by commercial and non-commercial relevance to analyze the characteristics of the folk taxonomy of artisanal fisheries in the lower La Plata river basin (Argentina). The photographs were shown to 60 artisanal fishers from the Paraná and Uruguay Rivers. Out of a set of 332 folk names recorded, monotypic names (79%) prevailed and over-differentiation (68%) was the most frequent correspondence among generic folk names. Morphology (68%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…As we discuss below, analogies to things, animals, and, to a lesser extent, shape also occur; names referring to habitat are also important for identifying specific fish. This is comparable with other ethno-taxonomic studies in small-scale fisheries (Aigo and Ladio 2016;Batista et al 2016;Begossi et al 2008;Castillo et al 2018;Clauzet et al 2007).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As we discuss below, analogies to things, animals, and, to a lesser extent, shape also occur; names referring to habitat are also important for identifying specific fish. This is comparable with other ethno-taxonomic studies in small-scale fisheries (Aigo and Ladio 2016;Batista et al 2016;Begossi et al 2008;Castillo et al 2018;Clauzet et al 2007).…”
Section: Discussionsupporting
confidence: 91%
“…This is partly because agencies and academics lack appreciation of the importance of such ethno-ichthyological data. In addition, conventional management approaches tend to undervalue fisher's knowledge in various ways (Castillo et al 2018). Research has been limited by a shortage of experts in the field, cultural barriers, and changing political and institutional scenarios (Baigún 2015;Castillo et al 2016).…”
Section: Ethnoichthyology Of Fishing Communities In the Lower Valley mentioning
confidence: 99%
“…The approache used in this study was EAF, considering fishers’ ecological knowledge (FEK) crucial to practical application in management plans (Leite and Gasalla 2013 ; Fischer et al 2015 ). FEK comprises experimental and experience based knowledge, of ecosystems and fisheries and changes in dynamics of fisheries -spatial and temporal issues related to SSF, on the status of population, exploitation and trends of resources-, fishing practices, communities, and the livelihoods (Bevilacqua et al 2016 ; Lima et al 2017 ; Castillo et al 2018 ). This proved to be useful for the definition of fishing grounds, fish habitats, to design conservation strategies for vulnerable species, and mitigating environmental conflicts (Castello et al 2009 ; Truchet and Noceti 2021 ; Truchet et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This limits the opportunity to apply the Ecosystem Approach to Fisheries (EAF; FAO 2019 ). Among other proposals, the EAF has suggested co-management as a new way of governance to overcome the specific limitations of the current legal frameworks of conventional management, highlighting the role of users in this scheme (Fischer et al 2015 ; Castillo et al 2016 ; 2018 ; FAO 2019 ). Under this approach, the value of local fishers’ ecological knowledge (FEK) on conservation and management is crucial, mostly in the case of SSF in developing countries, where scientific data or fiscal records are often scarce (Johannes et al 2000 ; Fischer et al 2015 ; Bevilacqua et al 2016 ; Castillo et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The higher level of specificity identifies the importance of these species to indigenous peoples. For freshwater systems, Castillo et al (2018) found that fishers in the Parana River were able to correctly identified 87 species that were grouped in 322 folk names.…”
Section: What Is Traditional Fishing Knowledge?mentioning
confidence: 99%